Principles of formation of the content of an educational electronic resource on the basis of general and didactic patterns of learning - Zaslavskaya, O.Y. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2018)
The article considers the influence of the development of technical means of teaching on the effectiveness of educational and methodical resources. Modern opportunities of information and communication technologies allow creating electronic educational resources that represent educational information that automates the learning process, provide information assistance, if necessary, collect and process statistical information on the degree of development of the content of the school material by schoolchildren, set an individual trajectory of learning, and so on. The main principle of data organization is the division of the training course into separate sections on the thematic elements and components of the learning process. General regularities include laws that encompass the entire didactic system, and in specific (particular) cases, those whose actions extend to a separate component (aspect) of the system. From the standpoint of the existence of three types of electronic training modules in the aggregate content of the electronic learning resource - information, control and module of practical classes - the principles of the formation of the electronic learning resource, in our opinion, should regulate all these components. Each of the certain principles is considered in the groups: scientific orientation, methodological orientation, systemic nature, accounting of interdisciplinary connections, fundamentalization, systematic and dosage sequence, rational use of study time, accessibility, minimization, operationalization of goals, unified identification diagnosis.